Lengthwise regional mechanics of the human aneurysmal ascending thoracic aorta. (May 2023) - Tarraf, Samar A.; Kramer, Benjamin; Vianna, Emily; Gillespie, Callan; Germano, Emídio; Emerton, Kelly B.; Amini, Rouzbeh; Colbrunn, Robb; Hargrave, Jennifer; Roselli, Eric E.; Bellini, Chiara
Abstract: The prognosis of patients undergoing emergency endovascular repair of ascending thoracic aortic aneurysm (ATAA) depends on defect location, with root disease bearing worse outcomes than proximal or distal aortopathy. We speculate that a spatial gradient in aneurysmal tissue mechanics through the length of the ascending thoracic aorta may fuel noted survival discrepancies. To this end, we performed planar biaxial testing on 153 root, proximal, and distal segments of ATAA samples collected from 80 patients receiving elective open surgical repair. Following data averaging via surface fitting-based interpolation of strain-controlled protocols, we combined in-vitro and in-vivo measurements of loads and geometry to resolve inflation-extension kinematics and evaluate mechanical metrics of stress, stiffness, and energy at consistent deformation levels. Representative (averaged) experimental data and simulated in-vivo conditions revealed significantly larger biaxial stiffness at the root compared to either proximal or distal tissues, which persisted as the entire aorta stiffened during aging. Advancing age further reduced biaxial stretch and energy storage, a measure of aortic function, across all ATAA segments. Importantly, age emerged as a stronger predictor of tissue mechanics in ATAA disease than either bicuspid aortic valve or connective tissue disorders. Besides strengthening the general understanding of aneurysmal disease, our findings provide specifications to customize the design of stent-grafts for the treatment of ATAA disease. Optimization of deployment and interaction of novel endovascular devices with the local native environment is expected to carry significant potential for improving clinical outcomes. Statement of significance: Elucidating the lengthwise regional mechanics of ascending thoracic aortic aneurysms (ATAAs) is critical for the design of endovascular devices tailored to the ascending aorta. Stent-grafts provide a less invasive alternative to support the long-term survival of ATAA patients ineligible for open surgical repair. In this study, we developed a numerical framework that combines semi-inverse constitutive and forward modeling with in-vitro and in-vivo data to extract mechanical descriptors of ATAA tissue behavior at physiologically meaningful deformation. Moving distally from the aortic root to the first ascending aortic branch, we observed a progressive decline in biaxial stiffness. Furthermore, we showed that aging leads to reduced aortic function and is a stronger predictor of mechanics than either valve morphology or underlying syndromic disorder. Graphical abstract: